Radiation hardness studies of AMS HV-CMOS 350 nm prototype chip HVStripV1 - Kanisauskas, K; Affolder, A; Arndt, K; Bates, R; Benoit, M; Bello, F; Blue, A; Bortoletto, D; Buckland, M; Buttar, C; Caragiulo, P; Das, D; et al. (IOP Publishing, 2017)
CMOS active pixel sensors are being investigated for their potential use in the ATLAS inner tracker upgrade at the HL-LHC. The new inner tracker will have to handle a significant increase in luminosity while maintaining a sufficient signal-to-noise ratio and pulse shaping times. This paper focuses on the prototype chip "HVStripV1" (manufactured in the AMS HV-CMOS 350nm process) characterization before and after irradiation up to fluence levels expected for the strip region in the HL-LHC environment. The results indicate an increase of depletion region after irradiation for the same bias voltage by a factor of ≈2.4 and ≈2.8 for two active pixels on the test chip. There was also a notable increase in noise levels from 85 e− to 386 e− and from 75 e− to 277 e− for the corresponding pixels.